Utopie und Politik: Potenziale kreativer Politikgestaltung - Maahs, Ina-Maria (transcript, 2019)
A precise analysis of political utopias in literature and practice shows not only the topicality of utopia, but also its potential for creative policy-making that is innovative, sustainable and oriented towards the common good.